ZINC AND ΑLPHA-LIPOIC ACID ALLEVIATE CYPERMETHRIN INDUCED REPRODUCTIVE TOXICITY IN MATURE MALE WISTAR RAT: Pharmaceutical Science-Pharmacology - BEPARI, MADHUBANTI; MAITY, PRALAY; DAS, TUHINA; MAITI CHOUDHURY, SUJATA (International Journal of Life Science and Pharma Research, 2014)
Cypermethrin (α- Cyano-3-Phenoxybenzyl (+ cis, trans) 3-(2, 2-Dichlorovinyl)-2, 2-dimethyl cyclopropane carboxylate) is an active pyrethroid which intensively controls a wide range of pests in agriculture and an ecto-parasiticide in humans and animals. It has moderate carcinogenic, mutagenic, immunosuppressive and hepatotoxic effects. It causes brain and locomotor disorders, polyneuropathy. The present study was conducted to evaluate the adverse effects of cypermethrin on the reproductive system of male Wistar rats, and also to assess the alleviating role of zinc and α-lipoic acid under these toxic conditions. Male Albino Wistar rats received oral cypermethrin treatment at two dose levels(40 mg/kg body wt,80 mg/kg body wt) and combined cypermethrin, zinc (227 mg/l in drinking water), and α-lipoic acid (35 mg/kg body wt) treatments for consecutive 14 days. The effects of the treatments were studied on some reproductive markers in rat testis including antioxidant parameters. Cypermethrin reduced the testicular index, sperm motility of rats of cypermethrin treated groups. Significant increase in seminal fructose concentration, testicular glutamate oxaloacetate transaminase (GOT), glutamate pyruvate transaminase (GPT), testicular malon-dialdehyde (MDA) level were seen whereas reduced glutathione (GSH) level and superoxide dismutase (SOD) activity of testis were decreased significantly in a dose-dependent manner compared to the control group. The present study showed that zinc and α-lipoic acid supplementation restored the altered reproductive parameters towards normal levels. The results revealed the beneficial influences of zinc and α-lipoic acid in reducing the harmful effects of cypermethrin on male reproductive system of rat.